Technique for Authenticating H.264/SVC Streams in Surveillance Applications - ZHUO, Wei (Institutional Knowledge at Singapore Management University, 2013)
Surveillance codestreams coded by H.264/SVC (scalable video coding), which consists of one base layer and one or more enhancement layers, supply flexible and various quality, resolution, and temporal (sub)codestreams such that clients with different network bandwidth and terminal devices can seamlessly access them. In this paper, we present a robust authentication scheme for them in order to insure the integrity of SVC surveillance codestreams, named AUSSC (Authenticating SVC Surveillance Codestreams). AUSSC exploits cryptographic-based authentication for base layer and content-based authentication for enhancement layers. For content-based authentication, AUSSC extracts full features from the first frame of each GOP (group of picture) and partial features from “active” macroblocks of other frames. Performance analysis indicates that AUSSC is robust to content-preserving manipulations and sensitive to content-changing manipulations of enhancement layers. Compared with cryptographic-based and watermarking-based authentication schemes, experimental results show that AUSSC causes less computation complexity and smaller compression overhead. Thus, it appears that AUSSC is suitable for real time SVC surveillance applications.